Rapid response action : Rehabilitation of the agricultural rural communities in Antigua and Barbuda in the aftermath of the Hurricane Irma - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The Rapid Response Action (RRA) was proposed by the IICA Office in Antigua and Barbuda in response to the damages caused by Hurricane Irma in the agricultural sector. The agricultural sector was heavily affected with significant damage to farms, on-farm infrastructure and farm access roads. Preliminary estimates provided by the Ministry of Agriculture and Fisheries indicated that the total loss to the agriculture sector was approximately US$ 1.7 million. Livestock damage (comprised by goats, sheep, pigs and poultry) are estimated at US$95,222.22 and damage to infrastructure is estimated at US$52,925.92 (including fencing, henhouses, garden beds, irrigation, etc.,). Losses are largely attributed to a temporary loss of home production and the additional costs associated with purchasing agricultural products.